An extensible model for historical financial data with an application to German company and stock market data - Dennis Gram; Pantelis Karapanagiotis; Jan Krzyzanowski; Marius Liebald; Uwe Walz (Leibniz Institute for Financial Research SAFE, 2021)
Broad, long-term financial and economic datasets are a scarce resource, in particular in the European context. In this paper, we present an approach for an extensible, i.e. adaptable to future changes in technologies and sources, data model that may constitute a basis for digitized and structured longterm, historical datasets. The data model covers specific peculiarities of historical financial and economic data and is flexible enough to reach out for data of different types (quantitative as well as qualitative) from different historical sources, hence achieving extensibility. Furthermore, based on historical German company and stock market data, we discuss a relational implementation of this approach.
Keywords: C81; C82; 330